2012
DOI: 10.1186/2008-2231-20-78
|View full text |Cite
|
Sign up to set email alerts
|

Somatic complaints and refrain from buying prescribed medications. Results from a cross-sectional study on people 60 years and older living in Kaunas (Lithuania)

Abstract: BackgroundThe use of medicines by elderly people is a growing area of concern in social pharmacy. A significant proportion of older people do not follow the recommendations from physicians and refrain from buying prescribed medications. The aim of this study is to evaluate associations between self-rated health, somatic complaints and refraining from buying prescribed medications by elderly people.FindingsData was collected in a cross-sectional study in 2009. We received 624 completed questionnaires (response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Nonadherence is a global issue (Cramer, 2004; Stankuniene et al, 2012; Kleinsinger, 2018). A meta-analysis of 20 studies conducted between 1998 and 2010 in Australia, Canada, the USA, and Europe to assess the extent of adherence of cardiovascular patients to their regimens indicated that approximately 50% were not properly adherent to cardiovascular medications prescribed for preventive purposes (Naderi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nonadherence is a global issue (Cramer, 2004; Stankuniene et al, 2012; Kleinsinger, 2018). A meta-analysis of 20 studies conducted between 1998 and 2010 in Australia, Canada, the USA, and Europe to assess the extent of adherence of cardiovascular patients to their regimens indicated that approximately 50% were not properly adherent to cardiovascular medications prescribed for preventive purposes (Naderi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Basic characteristics of the healthcare system and pharmaceutical schemes in each country are presented in Table 1 [ 10 – 18 ]. Some papers on use and non-adherence have been published elsewhere [ 19 22 ]. However, the referred papers have examined the prevalence of refrain due to any cause [ 19 ], or focused on the situation in Lithuania [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some papers on use and non-adherence have been published elsewhere [ 19 22 ]. However, the referred papers have examined the prevalence of refrain due to any cause [ 19 ], or focused on the situation in Lithuania [ 20 22 ]. In this paper, we investigate the prevalence of refrain due to financial problems among older persons and to compare it among seven European urban communities.…”
Section: Introductionmentioning
confidence: 99%